2016
DOI: 10.5121/ijcga.2016.6301
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Position-Based Fluids: Improving Performance of Fluid Simulations for Real-Time Applications

Abstract: The Position Based Fluids (PBF) method is a state-of-the-art approach for fluid simulations in the context

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Solenthaler and Gross proposed a two-scale particle simulation technique that handles particles in the deep region coarsely and finely handles particles in the shallow region [54]. This technique has been extended to many fields, such as a technique that can handle adaptive resolution in multiphase SPH method [55] and an adaptive SPH technique for real-time simulation [56], [57]. However, since these techniques try to optimize the number of particles and the amount of calculation through particle splitting and merging, their aim is different from the proposed method.…”
Section: Comparison Between Our Methods and Previous Approachesmentioning
confidence: 99%
“…Solenthaler and Gross proposed a two-scale particle simulation technique that handles particles in the deep region coarsely and finely handles particles in the shallow region [54]. This technique has been extended to many fields, such as a technique that can handle adaptive resolution in multiphase SPH method [55] and an adaptive SPH technique for real-time simulation [56], [57]. However, since these techniques try to optimize the number of particles and the amount of calculation through particle splitting and merging, their aim is different from the proposed method.…”
Section: Comparison Between Our Methods and Previous Approachesmentioning
confidence: 99%
“…Based on PBF, Köster and Kruger 34 presented a method to achieve remarkable improvements in Figure 4: Rigid body simulations. Top: a collision scene with 2000 rigid bodies colliding with each other and the ground.…”
Section: Fluid Simulationmentioning
confidence: 99%
“…Its highquality performance on cloth 29,30 has been well proven. However, it was later found that PBH 33 , integrating with SPH 31 , could also have visual plausibility in fluid simulation while inheriting the advantages of PBD [33][34][35] . Rigid body simulation is now being emphasized since it requires both deformations brought by particle systems and solid attributes.…”
Section: Rigid Body Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the particlestrength exchange phenomenon, Zhang et al [17] resolved the fluid boundary layers issues in fluid simulations. Koster et al [18] improved the performance of real-time fluid simulations with an adaptive position-based method. Chu et al [19] has used the CNN-based feature descriptors to implement an efficient data-driven approach for smoke flow simulations.…”
Section: Introductionmentioning
confidence: 99%